Magnetohydrodynamics - Bavdaž, Nina (Matrika, 2021)
Magnetohydrodynamics studies the behavior of an electrically conductive fluid in a magnetic field. The first part of the article presents the basics of magnetohydrodynamics. Noncentral collisions of heavy particles cause the formation of a very strong magnetic field in the quark-gluon plasma. With some assumptions, one can calculate this magnetic field. Finally, the result of how the magnetic field behaves in a vacuum and in the presence of a conductive medium is shown.
Keywords: hidrodinamika; hydrodynamics; kvark gluonska plazma; magnetic field; magnetno polje; quark-gluon plasma